Relationship between in feed drugs, antibiotics and organic enrichment in marine sediments at Canadian Atlantic salmon aquaculture sites. (March 2023) - Kingsbury, M.V.; Hamoutene, D.; Kraska, P.; Lacoursière-Roussel, A.; Page, F.; Coyle, T.; Sutherland, T.; Gibb, O.; Mckindsey, C.W.; Hartog, F.; Neil, S.; Chernoff, K.; et al.
Abstract: The presence of in-feed anti-sea lice drugs and their relationship with organic enrichment is poorly understood in sediment surrounding salmon farms. Using data from an aquaculture monitoring program (2018–2020), we describe this relationship at ten sites in four Canadian provinces. Three anti-sea lice pesticides (lufenuron, teflubenzuron, emamectin benzoate and metabolite desmethyl emamectin benzoate), and one antibiotic (oxytetracycline) were detected. Concentrations were often below limits of quantification. Values are also lower than those reported in other aquaculture salmon-producing countries. Highest concentrations, along with organic enrichment, were observed ~200 m of cages with lower concentrations detected up to 1.5 km away. Most samples had at least two drugs present: 75.2 % (British Columbia), 91.4 % (Newfoundland), and 54.8 % (New Brunswick/Nova Scotia) highlighting the potential for cumulative effects. Emamectin benzoate and oxytetracycline were detected four and three years respectively after last known treatments, demonstrating the need for research on overall persistence of compounds. Graphical abstract: Unlabelled Image Highlights: Sediment data collected through an aquaculture monitoring program were used. Three anti-sea lice drugs and one antibiotic were detected at ten salmon sites. The highest concentrations and organic enrichment were observed within 200 m of cages. Most sediment samples had at least two drugs present. There is a significant patchiness in drug presence and organic matter enrichment.